Investigating the Role of Youtube in the World of Education During a Pandemic - Meriani, Maya Eva; Sari, Tri Novita (Yayasan Nurul Yakin Bunga Tanjung, 2022)
The purpose of this study was to analyze the process and learning outcomes of physics students at SMA Negeri 3 Tungkal Jaya through the application media, namely youtube. In this study, a descriptive method is used to analyze the data through a description of the influence of the youtube application media. This research begins with formulating a problem topic and analyzing the research results. Where from the data obtained, the analysis of the use of the youtube application to improve student learning outcomes in physics learning at SMA Negeri 3 Tungkal Jaya is able to improve student learning outcomes with an average percentage of the influence of the youtube application media, namely 60,43%.